Physical layer security of full-duplex relay-assisted D2D networks under outdated CSI - Jingjie SHEN; Guangqiu LI; Yancui LUO; Huizhi LIU (Dianxin kexue, 2023)
The relay aided device to device (D2D) network can improve the spectrum efficiency of D2D users and the physical layer security of cellular user (CU) by sharing spectrum with the cellular network.To further improve their performance, transmit antenna selection can be used at the base station and the relay node of the D2D link, and full duplex technology can be used in the relay node.However, due to the feedback delay and mobility, the channel state information (CSI) used for the antenna selection of cellular link and all D2D links may be outdated.For the physical layer security and reliability in the above scenario, security model of a full duplex relay aided D2D network was proposed in the presence of active eavesdropping and outdated CSI, in which the base station and relay nodes both used transmit antenna selection.The closed-expressions for outage probability, ergodic capacity, probability of non-zero secrecy capacity, secure outage probability, asymptotic secure outage probability of relay aided D2D networks were derived.The numerical calculation and simulation results show that the more the number of base station transmit antennas and relay jamming antennas are, the better the CU security performance is.The outdated CSI will deteriorate the outage and security performance of CU.